Cinder cones of Mount Slamet, Central Java, Indonesia - Igan S. SutawIdjaja; R. Sukhyar (Indonesian Journal on Geoscience, 2009)
http://dx.doi.org/10.17014/ijog.vol4no1.20096The Mount Slamet volcanic field in Central Java, Indonesia, contains thirty five cinder cones within an area of 90 sq. km in the east flank of the volcano. The cinder cones occur singly or in small groups, with diameter of the base ranges from 130 - 750 m and the height is around 250 m. Within the volcanic field, the cinder cones are spread over the volcanic area at the distance of 4 to 14 km from the eruption center of the Slamet Volcano. They are concentrated within latitudes 7°11’00” - 7°16’00” S,, and longitudes 109°15’00” - 109°18’00” E. The density of the cinder cones is about 1.5 cones/km2. Most of the cinder cones lie on the Tertiary sedimentary rocks along the NW-trending fault system and on radial fractures. The structural pattern may be related to the radial faults in this region. The cone surfaces are commonly blanketed by Slamet air-falls and lava flows. The deposits consist of poorly bedded, very coarse-grained, occasionally overlain by oxidized scoria, and large-sized of ballistic bombs and blocks. There are various kind of volcanic bombs originating from scoriae ballistic rock fragments. The other kind of volcanic bombs are breadcrust bomb, almond seed or contorted shape. All of the cinder cones have undergone degradation, which can be observed from the characters of gully density and surface morphology. By using Porter parameters, Hco is equal to 0.25 Wco, whilst Wcr is equal to 0.40 Wco. The Hco/Wco ratio is higher than Hco = 0.2 Wco reference line. A radiometric dating using K-Ar method carried out on a scoria bomb yields the age of 0.042 + 0.020 Ma.